Learning while Traveling: Influences of Short-term Cross-cultural Immersion Experiences to High School Students - Bernadette Bugtong (Diversitas Journal)
This present study explored the experiences of Filipino learner-participants in a 6-day cross-cultural immersion held in Indonesia, aiming to understand how they interpreted their cultural learning over a year later.  Employing phenomenology as the research design, data was collected through in-depth interviews, focus group discussion, participant observation and document analysis.  The findings indicate that interactions with the host community helped participants recognize cultural diversity, respect cultural differences and reassess their cultural prejudices, leading to lasting changes in their perceptions and behaviors after returning home. However, the limitations brought by the restrictions on movements due to the COVID-19 pandemic, and the lack of pre-immersion and post-immersion activities have presented challenges to the breadth and depth of these changes. These findings underscore not only the importance of cross-cultural immersions in fostering intercultural sensitivity and competence but also the significance of continuous guidance from educators during the different stages of the experience. Furthermore, it was shown that despite the short time spent in the immersion, significant changes were still experienced by the participants, contrary to what some studies suggest.